2022
DOI: 10.48208/headachemed.2021.50
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre comportamento alimentar e hábitos de vida e aumento de crises de migrânea em universitários na pandemia da COVID-19

Abstract: Introdução: A pandemia da COVID-19 provocou alterações nos hábitos de vida e padrão alimentar da população, importantes gatilhos para as crises migranosas. Objetivo: Avaliar a associação entre comportamento alimentar e hábitos de vida e aumento das crises de migrânea em universitários na pandemia da COVID-19. Material e Métodos: Estudo descritivo, de corte transversal, retrospectivo, realizado com acadêmicos de universidade de Salvador, Bahia, entre dezembro/2020 a junho/2021. Os universitários foram convocado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The migraine parameters analyzed were frequency, intensity, pain impact, pain duration, time of diagnosis, symptoms, and duration of attacks, with the frequency and intensity of attacks being the two most evaluated factors by most of the studies included in this review. The frequency of migraines was present in 90% of the studies [1,2,6,[16][17][18][19]21,22]; in terms of intensity, it was evaluated in 30% of the studies [1,2,16]. However, there was no standardization in the parameters and instruments evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The migraine parameters analyzed were frequency, intensity, pain impact, pain duration, time of diagnosis, symptoms, and duration of attacks, with the frequency and intensity of attacks being the two most evaluated factors by most of the studies included in this review. The frequency of migraines was present in 90% of the studies [1,2,6,[16][17][18][19]21,22]; in terms of intensity, it was evaluated in 30% of the studies [1,2,16]. However, there was no standardization in the parameters and instruments evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between sleep disorders and migraines during the health crisis, 9 studies evaluated this lifestyle factor. Seven studies found a positive association with the frequency of migraine attacks, while one showed a relationship with intensity [1,2,6,[16][17][18][19]21,22]. Currò CT, et al [16] showed a positive association regarding the impact of pain.…”
Section: Association Between Sleep Disorders and Migrainesmentioning
confidence: 97%
See 3 more Smart Citations